Calculated plasma volume status and outcomes in patients undergoing coronary bypass graft surgery - Maznyczka, Annette Marie; Barakat, Mohamad Fahed; Ussen, Bassey; Kaura, Amit; Abu-Own, Huda; Jouhra, Fadi; Jaumdally, Hannah; Amin-Youssef, George; Nicou, Niki; Baghai, Max; Deshpande, Ranjit; Wendler, Olaf; et al. (Heart (British Cardiac Society), 2019)
ObjectivesCongestion is associated with worse outcomes in critically ill surgical patients but can be difficult to quantify noninvasively. We hypothesised that plasma volume status (PVS), estimated preoperatively using a validated formula that enumerates percentage change from ideal plasma volume (PV), would provide incremental prognostic utility after coronary artery bypass graft (CABG) surgery.MethodsIn this retrospective cohort study, patients who underwent CABG surgery (1999–2010) were identified from a prospectively collected database. Actual ([1-haematocrit] x [a+(b x weight [kg])]) and ideal (c x weight [kg]) PV were obtained from equations where a, b and c are sex-dependent constants. Calculated PVS was then derived (100% x [(actual−ideal)/ideal]).ResultsIn 1887 patients (mean age 67±10 years; 79% male; median European System for Cardiac Operative Risk Evaluation [EuroSCORE] 4), mean PVS was −8.2±9%. While 8% of subjects had clinical evidence of congestion, a relatively increased PV (PVS >0%) was estimated in 17% and correlated with lower serum sodium, higher EuroSCORE and a diagnosis of diabetes mellitus. A PVS≥5.6% was optimally prognostic and associated with greater mortality (HR: 2.31, p=0.009), independently of, and incremental to, EuroSCORE, New York Heart Association class and serum sodium. A PVS≥5.6% also independently predicted longer intensive care (β: 0.65, p=0.007) and hospital (β: 2.01, p=0.006) stays, and greater postoperative renal (OR: 1.61, p=0.008) and arrhythmic (OR: 1.29, p=0.03) complications.ConclusionsHigher PVS values, calculated simply from weight and haematocrit, are associated with worse inpatient outcomes after CABG. PVS could help refine risk stratification and further investigations are warranted to evaluate the potential clinical utility of PVS-guided management in patients undergoing CABG.